Devir corpo - Ambrosio, Leticia (Universidade Federal de São Carlos, 2017)
This text, which is presented as a Course Conclusion Paper, intends to gather in its composition a knowledge incorporated over five years while studying undergraduate in Occupational Therapy, at the Federal University of São Carlos - UFSCar. During these years, I looked at three theoretical references outside of Occupational Therapy to try to understand the human body - Nietzsche, Merleau-Ponty and Deleuze-, who will be my interlocutors almost all the time, as they have been in the last five years, as well as other interlocutors. occupational therapists who served as inspiration - Marcus Vinícius Machado de Almeida, Flávia Liberman, Elizabeth MFA Lima, Eliane Dias Castro, Mariângela Quarentei, among others. Lewis Carroll's writings on Alice and Wonderland will be part of this composition, because, through experiences lived by my own body, I found in Alice thousands of intensities, pulsations and identities that fit me for now and serve as an artistic representation of these experiences. Throughout the text, drawings, paintings and photographs will be presented which, like Alice's tale, serve me as an artistic representation, but in addition, they serve me as a representation closer to the reality of my body's experiences. After all, a book without illustrations is not a book, Alice
Becoming body
Devenir cuerpo
Keywords: Corpo; Corporeidade; Terapia Ocupacional; Body; corporeality; Occupational Therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL